Problems in the Evaluation of Islamic Religious Education Learning in the Digital Era and Efforts to Supervise Mobile Phone Usage - Nur Azizah; Ahmad Ibrahim Hasibuan; Yusman Yusman; Rahmaini Rahmaini; Iin Triana (Al-Fikru: Jurnal Ilmiah, 2026)
Advances in digital technology have transformed the evaluation process in Islamic Religious Education, shifting the focus of assessment from cognitive aspects to include affective and psychomotor aspects as well. However, digital-based evaluation still faces various challenges, such as low student integrity, smartphone misuse, limited supervision, disparities in technological proficiency, and internet connectivity issues. This study aims to analyze the challenges of assessment in Islamic Religious Education in the digital age, as well as strategies for monitoring smartphone use to enhance the effectiveness and integrity of assessment. The research employs a qualitative approach through a literature review, examining relevant journals and books. The results indicate that digital assessment offers efficiency and flexibility but also creates opportunities for academic dishonesty and learning distractions. To address these issues, schools implement strict supervision, restrictions on smartphone and app usage, the development of analysis-based questions, and the instillation of integrity values. Therefore, digital literacy and effective supervision are essential for supporting meaningful and accountable learning assessments in the digital age.